Upstream Ultra‐Low Frequency Waves Observed by MESSENGER's Magnetometer: Implications for Particle Acceleration at Mercury's Bow Shock. Issue 9 (7th May 2020) - Romanelli, N.; DiBraccio, G.; Gershman, D.; Le, G.; Mazelle, C.; Meziane, K.; Boardsen, S.; Slavin, J.; Raines, J.; Glass, A.; Espley, J.
Abstract: We perform the first statistical analysis of the main properties of waves observed in the 0.05–0.41 Hz frequency range in the Hermean foreshock by the MErcury Surface, Space ENvironment, GEochemistry, and Ranging (MESSENGER) Magnetometer. Although we find similar polarization properties to the "30 s" waves observed at the Earth's foreshock, the normalized wave amplitude ( δ B /| B0 | ∼0.2) and occurrence rate (∼0.5%) are much smaller. This could be associated with relatively lower backstreaming proton fluxes, the smaller foreshock size and/or less stable solar wind (SW) conditions around Mercury. Furthermore, we estimate that the speed of resonant backstreaming protons in the SW reference frame (likely source for these waves) ranges between 0.95 and 2.6 times the SW speed. The closeness between this range and what is observed at other planetary foreshocks suggests that similar acceleration processes are responsible for this energetic population and might be present in the shocks of exoplanets. Key Points: We perform the first statistical analysis (4, 536 events) of the main properties of the lowest‐frequency waves in the Hermean foreshock Small normalized wave amplitude (0.2) and occurrence (0.5%) are likely due to low backstreaming proton flux and variable external conditions The normalized backstreaming protons speed (∼0.95–2.6) suggests similar acceleration processes occur at several planetary shocks